Pengaruh dimensi perceived enjoyment terhadap behavioral intention pengguna game mobile legends bang:bang (komunitas esport UHASY) - Hasanudin (CV. ALIM'SPUBLISHING, 2023)
Abstract. This study aims to determine the effect of the perceived enjoyment dimension on behavioral intention. This research takes the object in the UNHASY Esport Community. The results of this study used Sampling Roscue because this study used correlation or multiple regression analysis, so the number of samples was at least 10 times the number of variables to be studied, therefore this study took 40 samples from 4 variables. The results showed (1) Pleasure has a partial effect on the Behavioral Intention of Mobile Legends Bang:Bang Game Users (UNHASY E-sport Community) (2) Enjoyable has a partial effect on the Behavioral Intention of Mobile Legends Bang:Bang Game Users (UNHASY E-sport Community) ) (3) Fun has a partial effect on the Behavioral Intention of Mobile Legends Bang:Bang Game Users (UNHASY E-sport Community) (4) Pleasure, Enjoyable, Fun has a simultaneous and significant effect on the Behavioral Intention of Mobile Legends Bang:Bang Game Users (Community UNHASY e-sport). Keywords: Pleasure, Enjoyable, Fun, Behavioral Intention.